2008
DOI: 10.1371/journal.pone.0002537
|View full text |Cite
|
Sign up to set email alerts
|

On the Prevalence of M. avium Subspecies paratuberculosis DNA in the Blood of Healthy Individuals and Patients with Inflammatory Bowel Disease

Abstract: BackgroundMycobacteria, such as M. leprae and M. tuberculosis infect billions of humans. However, because of appropriate immune responses and antibiotic therapy, overt mycobacterial diseases occur far less frequently. M. avium subspecies paratuberculosis (MAP) causes Johne's disease in ruminants, an affliction evocative of inflammatory bowel disease (IBD). Several agents used to treat IBD (5-ASA, methotrexate, azathioprine and its metabolite 6-MP) have recently been shown to be antiMAP antibiotics. We herein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
3
43
1
10
Order By: Relevance
“…MICs of the dihydrophthalazines for pneumococci, group A streptococci, and M. catarrhalis were far lower than those of Tmp and comparable to those of Lvx. The dihydrophthalazines also showed very interesting activities against M. avium, an established pulmonary pathogen (30,38) which has been implicated in inflammatory bowel diseases (22,29) and which is the subject of considerable effort vis-à-vis antifolate therapy (1,21). However, BAL0030543, BAL0030544, and BAL0030545 showed relatively poor in vitro activities toward H. influenzae.…”
Section: Discussionmentioning
confidence: 99%
“…MICs of the dihydrophthalazines for pneumococci, group A streptococci, and M. catarrhalis were far lower than those of Tmp and comparable to those of Lvx. The dihydrophthalazines also showed very interesting activities against M. avium, an established pulmonary pathogen (30,38) which has been implicated in inflammatory bowel diseases (22,29) and which is the subject of considerable effort vis-à-vis antifolate therapy (1,21). However, BAL0030543, BAL0030544, and BAL0030545 showed relatively poor in vitro activities toward H. influenzae.…”
Section: Discussionmentioning
confidence: 99%
“…Elguezabal et al [46] found a prevalence of 45.2% MAP DNA in the blood of healthy controls, compared to 21.38% and 19.04% in CD and UC patients respectively. The authors attributed the difference to therapy, as did Juste et al [48] , who found an even bigger difference between healthy controls (47% MAP DNA in blood) and IBD (16%). Juste et al [48] found that 17% of the patients receiving mesalamine, 6% of those taking sulfasalazine, and none of the ones taking methotrexate, mercaptopurine, ciprofloxacin or tacrolimus had MAP DNA detectable in blood; no difference was observed with azathioprine or steroids.…”
Section: Mycobacterium Avium Paratuberculosismentioning
confidence: 91%
“…Humans worldwide are highly exposed to MAP. MAP has been cultured from pasteurized milk, chlorinated potable water, meat products, breast milk from mothers with CD, and from the blood of IBD patients [46,48] and controls.…”
Section: Mycobacterium Avium Paratuberculosismentioning
confidence: 99%
“…Furthermore, the positive incidence is significantly higher in biopsies of terminal ileum and colon in CD patients than in those from healthy controls [67]. However, counteracting studies disproved such association [68][69][70][71]. Anti-MAP treatment with antibiotics does show short-term benefits in enhancing corticoid-induced remission, but hardly sustains the improvement over a longer course (156 weeks) [72].…”
Section: Pathogenic Bacteria Associated With Ibdmentioning
confidence: 99%